Efemeridade na arquitetura: a alternância de significado dos espaços públicos do centro paulistano na " Virada Cultural" - Costa, Vitor Mesquita Bringel da (2015)
The public places of the central region of São Paulo has become the focus of civil society, which seeks to "take back this places" promoting temporary cultural events of many expressions, among which the most relevant: the "Virada Cultural". The ephemeral architecture makes this event giving it structure and producing a redefinition of urban spaces in which it operates. In this context, this research focuses: the inclusion of ephemeral constructions in areas already established for cultural events. This work aims to analyze the redefinition process of urban space by observing the assembly and disassembly of environments at the Virada Cultural. For this purpose, previously approached the conceptual aspects and relevant theoretical study to investigate the object's context and gain knowledge on reading tools of nonverbal languages. Iconically were recorded photographically the chosen sites, all the different assembly processes environments, the occurrences before and during the events in order to capture the physical transformations applied to those spaces. From these observations and records conducted the graphical and analytical readings aimed at a deeper understanding of the changing meanings attributed to the chosen spaces. Moreover, the work investigated the capacities of composability construction systems employed in such ephemeral environments. The study reveals that the construction system used has high flexibility of composition and that basically syntactic additions by ephemeral structures in constant relationship with the permanent space provide new uses and engender the complex process of redefinition of public spaces at the Virada Cultural